TRACING THE SOURCES AND TRANSPORT PATHWAYS OF PARTICULATE IN JAKARTA USING THE WRF-HYSPLIT MODEL DURING THE JULY 2023 POLLUTION EPISODE - Ririn Anggina Batubara; Alvin Pratama; Amalia Nurlatifah (Jurnal Reka Lingkungan, 2026)
PM2.5 pollution remains a critical environmental and public health issue in Jakarta, particularly during the dry season when unfavorable meteorological conditions enhance pollutant accumulation. This study examines the sources and transport pathways of PM2.5 during a severe pollution episode in July 2023, utilizing a combined Weather Research and Forecasting (WRF) and Hybrid Single-Particle Lagrangian Integrated Trajectory (HYSPLIT) modeling approach. Meteorological simulations were evaluated against surface observations, while backward trajectory analyses were conducted using multiple meteorological datasets to assess the consistency of transport. The results indicate that PM2.5 transport into Jakarta was predominantly influenced by air masses originating from the east and southeast, associated with industrial activities, power plants, and local fire events in surrounding regions. The presence of the southeast monsoon contributed to reduced atmospheric dispersion, resulting in prolonged pollutant residence times over the urban area. Despite some limitations in wind speed simulation, the WRF model adequately represented key meteorological parameters relevant to trajectory analysis. These findings highlight that Jakarta’s air pollution is driven by the combined effects of local emissions and regional transport processes, emphasizing the need for integrated air quality management strategies that extend beyond administrative boundaries.